EMPLOYEE ENGAGEMENT SEBAGAI KUNCI MENINGKATKAN KINERJA KARYAWAN (International Journal Review) - Rachmawati, Meida (AMONG MAKARTI, 2013)
Abstract Employee engagement is a vast construct that touches almost all parts of human resource management facets we know hitherto. If every part of human resources is not addressed in appropriate manner, employees fail to fully engage themselves in their job in the response to such kind of mismanagement. The construct employee engagement is built on the foundation of earlier concepts like job satisfaction, employee commitment and Organizational citizenship behaviour. Though it is related to and encompasses these concepts, employee engagement is broader in scope. Employee engagement is stronger predictor of positive organizational performance clearly showing the two-way relationship between employer and employee ompared to the three earlier constructs: job satisfaction, employee commitment and organizational citizenship behaviour. Engaged employees are emotionally attached to their organization and highly involved in their job with a great enthusiasm for the success of their employer, going extra mile beyond the employment contractual agreement. Keywords: Employee engagement, Employee commitment, Organizational citizenship behaviour, Job satisfaction